A digital signal processor-based pulse programmer with performance of run-time information handling for magnetic resonance imaging. (30th April 2015) - Xiao, Liang; Li, Lin; Nie, Wei; Xie, Xiaoming; Wan, Hongjie
Abstract: A pulse programmer for magnetic resonance imaging based on a digital signal processor (DSP) is described. The pulse programmer not only implements event triggering and control line generation, but also performs the run-time information handling. The DSP, which has features that include a 32-bit data bus, a 24-bit address bus and a clock rate of 60 MHz, is used as the sequence operator. The DSP connects the field programmable gate array (FPGA) devices of all the spectrometer modules via its external bus, and manipulates the operation of each module via setting the control port of the corresponding FPGA. In addition, the run-time information of the spectrometer, which includes the operation status of each module and the external triggers, can be obtained easily using the read instruction, and the operation exceptions of the spectrometer can be treated quickly via the DSP's interrupt mechanism. Up to 32 control lines can be generated simultaneously in an event, and the minimum interval between successive events is 50 ns. The pulse sequence program is written in the C++ language and is mainly composed of several predefined procedures. The performance of the proposed pulse programmer is validated by multiple imaging experiments.